Fatal Knowledge? Prenatal Diagnosis and Sex Selection - Wertz, Dorothy C. (The Hastings Center report, 1989)
Moral and social arguments weigh heavily against performing medical procedures solely for purposes of sex selection. The medical profession has a responsibility to abandon its posture of ethical neutrality and take a firm stand now against sex selection.